Trinidad and Tobago in the spotlight - Manning, Patrick (2009)
Urges regional governments to use the opportunity of the 5th Summit of the Americas to generate greater global awareness of the potential of Trinidad and Tobago and the Caribbean, and to let the world know that these countries are open for business.